Spontaneous C. septicum gas gangrene: A literature review. (December 2017) - Srivastava, Ira; Aldape, Michael J.; Bryant, Amy E.; Stevens, Dennis L.
Abstract: As the infectious disease paradigm undergoes a subtle shift, unusual infections associated with malignancy and immunosuppression are being increasingly reported. Spontaneous or non-traumatic Clostridium septicum infection is one such unusual infection which has gained prominence. This article aims to understand the pathophysiology, clinical manifestations and current trends in diagnosing and treating this rare but deadly infection. To understand the multifactorial causation of this infection a review of published cases of spontaneous C. septicum gas gangrene was performed and a total of 94 such cases were identified. Several factors were analyzed for each case: age, infection location and underlying illness, presenting signs and symptoms, neutropenia, gross pathology of the colon, antibiotic use, surgical intervention, and survival. A known or occult malignancy was present in 71% patients and an overall mortality of 67% was observed. Highlights: This article summarizes the pathophysiology, clinical spectrum, diagnosis and management of spontaneous C. septicum infections. A systematic review and analysis is performed for published spontaneous C. septicum gas gangrene cases since 1956 to 2016. Reviewed data suggests that a known or occult malignancy was present in 71% cases. Pathophysiology of spontaneous C. septicum infection is discussed and gaps in the current understanding are identified